Peningkatan keterampilan peternakan pada narapidana ‎Lapas Kelas ‎IIB Sleman melalui program “Ayam Bahagia”‎ - Al-Fikri, Moh Fatih (Maliki Interdisciplinary Journal, 2023)
Ex-convicts who experience discrimination when looking for work are more likely to reoffend if they do not have or do not have the necessary skills. This problem is also faced by former convicts at the Class IIB Penitentiary in Sleman, Yogyakarta Special Region, so that some self-reliance and skill development, such as animal husbandry, is provided in the "Assimilation Village" for convicts. However, there are problems with laying hen breeders due to a lack of knowledge about good management practices among correctional officers as facilitators. To solve this, program "Ayam Bahagia" program was created to give correctional authorities and inmates the knowledge and practical skills they need to manage the raising of laying hens properly and effectively.The program encompassed the planning, execution, monitoring, and evaluation through a hybrid delivery approach that used both offline and online.